Mapping The Rate Of Deforestation In South Kalimantan Using Landsat Imagery (EarthCare, 2022)
South Kalimantan Province is an area that has a very large forest area, but this forest continues to decrease due to deforestation. Deforestation continues to be one of the factors causing flooding. Flooding in this area is a recurring disaster that must be overcome. For this reason, it is necessary to calculate changes in forest area so that forest processing can be carried out properly and that banners can be overcome. In this study, the rate of deforestation was calculated using a map of land use change in South Kalimantan Province through the google earth engine platform using Landsat imagery. The method in this research is supervised classification, which is taking polygon samples in land use classification. The image classification algorithm with javascript on the google earth engine platform will classify the same pixel values into the same classification based on the samples that have been made. Through this platform, images in geo.tif format will be obtained. then the image is processed using ArcGIS software to process the image into a map and the area of each classification. This map was then overlaid between 2015, 2018, and 2020 to see the changes. Based on the results of the study, it was found that there was a change in land use, especially in the forest class and community plantations. Forests decreased to 311,255 hectares with a decreasing rate of 62,251 hectares every year, while community plantations increased by 328,858 hectares with an increase of 65,771 hectares every year.